Effects of Additional Low-Pass–Filtered Speech on Listening Effort for Noise-Band–Vocoded Speech in Quiet and in Noise - Pals, Carina (Ear Hear, 2019)
OBJECTIVES: Residual acoustic hearing in electric–acoustic stimulation (EAS) can benefit cochlear implant (CI) users in increased sound quality, speech intelligibility, and improved tolerance to noise. The goal of this study was to investigate whether the low-pass–filtered acoustic speech in simulated EAS can provide the additional benefit of reducing listening effort for the spectrotemporally degraded signal of noise-band–vocoded speech. DESIGN: Listening effort was investigated using a dual-task paradigm as a behavioral measure, and the NASA Task Load indeX as a subjective self-report measure. The primary task of the dual-task paradigm was identification of sentences presented in three experiments at three fixed intelligibility levels: at near-ceiling, 50%, and 79% intelligibility, achieved by manipulating the presence and level of speech-shaped noise in the background. Listening effort for the primary intelligibility task was reflected in the performance on the secondary, visual response time task. Experimental speech processing conditions included monaural or binaural vocoder, with added low-pass–filtered speech (to simulate EAS) or without (to simulate CI). RESULTS: In Experiment 1, in quiet with intelligibility near-ceiling, additional low-pass–filtered speech reduced listening effort compared with binaural vocoder, in line with our expectations, although not compared with monaural vocoder. In Experiments 2 and 3, for speech in noise, added low-pass–filtered speech allowed the desired intelligibility levels to be reached at less favorable speech-to-noise ratios, as expected. It is interesting that this came without the cost of increased listening effort usually associated with poor speech-to-noise ratios; at 50% intelligibility, even a reduction in listening effort on top of the increased tolerance to noise was observed. The NASA Task Load indeX did not capture these differences. CONCLUSIONS: The dual-task results provide partial evidence for a potential decrease in listening effort as a result of adding low-frequency acoustic speech to noise-band–vocoded speech. Whether these findings translate to CI users with residual acoustic hearing will need to be addressed in future research because the quality and frequency range of low-frequency acoustic sound available to listeners with hearing loss may differ from our idealized simulations, and additional factors, such as advanced age and varying etiology, may also play a role.